Antioxidant and Antibacterial Assay of Virgin Coconut Oil-Olive Oil Blend - Rawiningyas, Sotya; Djasmasari, Wittri; Yuliana, Eva; Supriatna, Dadang; Sirait, Shinta Damerys; Permana, M.Si., Dr. Anita Herawati (Politeknik AKA Bogor, 2025)
Virgin coconut oil (VCO) has bioactivity that benefits health, such as lowering cholesterol, anti-inflammatory and antibacterial. Antibacterial properties of VCO related to the content of lauric acid. However, VCO has a poor physicochemical resistance. One way to improve the quality of VCO is to add antioxidant compounds, such as olive oil (OO), which has high antioxidants. This study used a blend of VCO and OO with 10% OO composition (OO10). The addition of olive oil resulted in a lower IC50 of the VCO-OO blend (41,666 ppm) compared to the pure VCO (125,000 ppm), thus suggesting that the VCO-OO blend has higher antioxidant capacity. However, neither VCO, OO nor OO10 blend showed antibacterial activity against Escherichia coli and Staphylococcus aureus.